THE LATE AMENDMENT OF PLEADINGS – TIME FOR A NEW APPROACH? Randa v Radopile Projects CC 2012 (6) SA 128 (GSJ) - Thino Bekker (Obiter, 2017)
Section 34 of the Constitution encapsulates the ideal of access to justice in civil matters, and provides that everyone has the right to have any dispute that can be resolved by the application of law, decided in a fair public hearing before a Court or, where appropriate, another independent and impartial tribunal or forum. This includes the requirement that the duration and costs of civil litigation should be reasonable. Unfortunately this objective is sometimes defeated by unnecessary and costly delays, due to tactical and careless postponements of civil matters in both the high and magistrates’ courts. One of the main culprits in this regard is the procedure of the amendment of pleadings after a trial has commenced. Our courts have always followed a very liberal approach in this regard in that an application for amendment will usually succeed, unless it is made mala fide or will lead to prejudice to the opponent, which cannot be cured by a cost order and, where appropriate, a postponement. In Randa v Radopile Projects CC (2012 (6) SA 128 (GSJ)), Willis J advocated a new approach in deciding of whether an application for an amendment should be granted. This approach is also in line with the latest developments in England, where the Courts recently favoured a more conservative approach in relation to applications for amendments at a late stage. This case note will firstly focus on a brief discussion of the historical development of the Court’s discretion in allowing amendments to pleadings. Secondly, the decision in Randa will be critically analysed. Thirdly, the latest developments in the English law will be discussed, and, lastly, some alternatives will be considered for legal reform. It will be argued that the Supreme Court of Appeal should alter its approach to the late amendment of pleadings in favour of a more conservative approach, as evidenced by the current English approach, alternatively that the legislature should intervene to capture the scope and ambit of a Court’s discretion in deciding whether an application for the amendment of a pleading after the commencement of a trial, should succeed.